Diagnostic value of dual-tracer PET/CT with [18F]FDG and PSMA ligands in prostate cancer: an updated systematic review - Iacovitti, Cesare Michele; Cuzzocrea, Marco; Rizzo, Alessio; Bauckneht, Matteo; Delgado Bolton, Roberto C.; Paone, Gaetano; Treglia, Giorgio (Frontiers in Medicine, 2025)
BackgroundProstate-specific membrane antigen (PSMA) ligand PET/CT has significantly improved prostate cancer (PCa) imaging. However, in patients with poorly differentiated PCa or neuroendocrine transdifferentiation, [18F]fluorodeoxyglucose ([18F]FDG) PET/CT may provide additional diagnostic information. This systematic review evaluates the diagnostic value of combining [18F]FDG PET/CT with PSMA ligand PET/CT in PCa patients.MethodsA systematic literature search of studies assessing the added diagnostic value of dual-tracer [18F]FDG and PSMA ligands PET/CT in PCa patients was conducted using PubMed/MEDLINE and Cochrane Library databases and available information was summarized.ResultsFourteen studies (n = 901 patients) met the inclusion criteria. The dual-tracer approach identified [18F]FDG-positive/PSMA-negative (FDG+/PSMA−) lesions in a subset of patients, particularly those with Gleason Score (GS) ≥ 9. However, in patients with GS < 8, [18F]FDG PET/CT did not significantly improve lesion detection over PSMA ligand PET/CT alone.The presence of FDG+/PSMA− lesions correlated with aggressive tumor biology, increased risk of metastases, and worse prognosis.ConclusionLiterature data showed that [18F]FDG PET/CT may serve as a valuable complementary imaging modality for high risk PCa patients potentially influencing staging and treatment decisions. Future prospective studies are warranted to further elucidate the prognostic significance and cost-effectiveness of combining [18F]FDG PET/CT with PSMA ligand PET/CT in PCa patients.